1994
DOI: 10.1177/008124639402400409
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Scores on Test Anxiety and Academic Achievement among South African University Graduate Students

Abstract: Past research has shown a relationship between gender and test anxiety as well as between academic achievement and test anxiety. Women score higher than men on test anxiety and people who score higher on such measures have been found to perform less well academically than those who score low. The purpose ofthis study was to investigate gender differences, specifically whether test anxiety would be associated with African students' academic achievement. The results showed a small though significant sex differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…This result is in consonance with the findings of Cassady and Johnson (2002), Mwamwenda (1994), Olatoye and Afuwape (2003), Razor and Razor (1998), and Zeidner (1998) which reveal that female students experienced higher test anxiety than their male counterparts. That females reported higher level of CBT anxiety than their male counterparts is not surprising, because females seem to be more emotional, have less self-control, and often perceive evaluative situations as more threatening than their male counterparts (Akanbi, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is in consonance with the findings of Cassady and Johnson (2002), Mwamwenda (1994), Olatoye and Afuwape (2003), Razor and Razor (1998), and Zeidner (1998) which reveal that female students experienced higher test anxiety than their male counterparts. That females reported higher level of CBT anxiety than their male counterparts is not surprising, because females seem to be more emotional, have less self-control, and often perceive evaluative situations as more threatening than their male counterparts (Akanbi, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, while Akanbi (2013), Falaye (2010), Mwamwenda (1993, Olatoye (2007), and Onyeizugbo (2010) reported non-significant gender differences in test anxiety, Cassady and Johnson (2002), Mwamwenda (1994), Olatoye and Afuwape (2003), Razor andRazor (1998), andZeidner (1998) reported that female students consistently showed high test anxiety than male students. Going by the mixed and inconclusive results on gender differences in test anxiety and dearth of empirical studies on gender and CBT anxiety in Nigeria, there is a need to further investigate gender differences in CBT anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Even the faculty members need to be trained to understand these factors and help the students in better academic performance. Mwamwenda (1994) in his study found that highly test-anxious students performed poorly regardless of the amount of exam preparation. Other Researchers have also established that people with high levels of anxiety are associated with low academic achievement (Idaka, Egbona, & Bassey, 2011;Rana & Mahmood, 2010;Yousefi, Talib, Mansor, Juhari, & Redzuan, 2010;Zeidner & Safir, 2001;Williams, 1996).…”
mentioning
confidence: 96%
“…In this way researchers reported students that educated purifying, comprehension and the understanding of cognition aspects have less test anxiety than to groups that watched film about test anxiety and the group that had studied the reports to this syndrome [19]. And also in a research that did by [20] resulted that if students have skull duggery paper in test session their test anxiety decrease significant.…”
Section: Introductionmentioning
confidence: 96%